The Scarcity Slot Excavating Histories of Food Security in Ghana - Logan, Amanda L. (University of California Press, 2020)
A free open access ebook is available upon publication. Learn more at www.luminosoa.org.The Scarcity Slot is the first book to critically examine food security in Africa's deep past. Amanda L. Logan argues that African foodways have been viewed through the lens of "the scarcity slot," a kind of Othering based on presumed differences in resources. Weaving together archaeological, historical, and environmental data with food ethnography, she advances a new approach to building long-term histories of food security on the continent in order to combat these stereotypes. Focusing on a case study in Banda, Ghana that spans the past six centuries, The Scarcity Slot reveals that people thrived during a severe, centuries-long drought just as Europeans arrived on the coast, with a major decline in food security emerging only recently. This narrative radically challenges how we think about African foodways in the past with major implications for the future.